Analisis Kepuasan Pengguna Layanan Tax Center Politeknik Negeri Jember - Sutantio, R. Alamsyah; Ardhiarisca, Oryza; Wijayanti, Rahma Rina; Harkat, Avisenna; Ghozali, Nur Azizah Wandinia; Ardiansyah, Diki; Pratiwi, Arti Febriani (Politeknik Ganesha Medan, 2024)
This research activity aims to conduct an analysis of service user satisfaction for Jember State Polytechnic Tax Center service users. It is hoped that the results of this research can provide suggestions for improving Tax Center services in the future. Respondents in this research were users of the Jember State Polytechnic Tax Center service. The number of respondents was determined using the Slovin equation so that the respondents in this study were 56 respondents. This research data was obtained by distributing questionnaires. The data obtained was analyzed for data quality through testing the validity and reliability of the data. Next, it will be analyzed further using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The research provides results showing that the level of satisfaction with using Tax Center services is within satisfaction with an index of 80.42%. To be able to improve services, several priority improvements are needed, namely attributes in Quadrant I. These attributes include access to position information about service procedures, technology systems, information containing all service procedures as well as instructions for filling out service documents, accessibility of Tax Center locations, schedules. definite service, as well as the discipline of tax volunteers in providing services